2019
DOI: 10.1038/s41405-019-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

Variations in AXIN2 predict risk and prognosis of colorectal cancer

Abstract: Objective Colorectal cancer (CRC) and hypodontia are frequent and different diseases with common genes are involved in their etiology. The objective of this study was to identify the association between AXIN2 rs2240308 with hypodontia and CRC. Patients and methods This study consisted of 50 individuals with hypodontia, 50 individuals with CRC, and 155 healthy individuals from Colombia. SNP genotyping assays of rs2240308 were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
1
14
0
2
Order By: Relevance
“…A genotyping study of AXIN2 rs2240308 polymorphism in 50 patients with CRC, 50 hypodontia patients and 155 healthy individuals revealed no significant relationship between this SNP and simultaneous occurrence of hypodontia and CRC. However, results suggest that AXIN2 rs2240308 polymorphism is associated with CRC 69 . Küchler et al 51 added to AXIN2 rs2240308 and rs740026 another 12 polymorphisms in FGF3 , FGF10 , and FGFR2 and all markers were genotyped in 82 individuals with tooth agenesis and 328 individuals with no defect of dentition.…”
Section: Tooth Agenesis As a Predictive Marker For Cancermentioning
confidence: 99%
“…A genotyping study of AXIN2 rs2240308 polymorphism in 50 patients with CRC, 50 hypodontia patients and 155 healthy individuals revealed no significant relationship between this SNP and simultaneous occurrence of hypodontia and CRC. However, results suggest that AXIN2 rs2240308 polymorphism is associated with CRC 69 . Küchler et al 51 added to AXIN2 rs2240308 and rs740026 another 12 polymorphisms in FGF3 , FGF10 , and FGFR2 and all markers were genotyped in 82 individuals with tooth agenesis and 328 individuals with no defect of dentition.…”
Section: Tooth Agenesis As a Predictive Marker For Cancermentioning
confidence: 99%
“…Previous studies evaluated the mentioned variant on patients with hypodontia and demonstrated that the presence of a variant allele was associated with frontal agenesis [29]. Also, the mentioned variant was previously associated with cancer risk, such as colorectal cancer [30], breast cancer [31], and Hirschsprung disease [32]. In the case of CHDs patients, other AXIN2 variants [c.28 C > T (p.L10F), c.395 A > G (p.K132R)] were previously reported by Zhu M et al [33] as pathogenic variants for CHDs.…”
Section: Discussionmentioning
confidence: 97%
“…The variations in WNT genes have been recognized in an individual with tooth agenesis (Dinckan et al, 2016). Therefore, the AXIN2 mutations could lead to an inefficient block of the WNT signaling pathway and altered the embryonic development of dental organs and predisposition to cancer (Otero et al, 2019). We hypothesized that reduced induction of FHIT might be triggering AXIN2 mutation and directly producing WNT dysregulation in the progression of lip and palate fusion and tooth development and finally leading to abnormal growth.…”
Section: Significant Copy Number Loss In Fhit Among Nscl/p With Hypodmentioning
confidence: 99%